Articulación espacial de la economía regional servicios y comercio como base para una zonificación económica en la zona aledaña sur del Parque Nacional Amboró - Gierhake, Klaus; Justus Liebig University Giessen (My University, 2003)
The study analyses the spatial impacts of public / private services and trade on the regional economy. Two different aspects are used in this context: an investigation on what is offered and, complementary to this, what is demanded. This approach might serve for a delimitation of buffer-zones and, in a broader sense, a methodology for economic zoning ('zonificación económica') and spatial occupation ('ocupación del territorio'), two planning instruments frequently discussed in Bolivia and Peru. The southern buffer-zone of the Amboró National Park (Departamento Sta. Cruz / Bolivia) serves as a case study. For that reason, a summary of regional characteristics is presented: population, land use and land tenure, social and economic infrastructure, principal objectives of development planning on the Departamento and the Province level. The following aspects can be resumed as main findings: - The study region is situated closely to one of the most dynamic economic centers, Sta. Cruz, and on the basis of functional relations depends on this center. The high intensity of transport to and from Sta. Cruz reflects this very well. - Considering the number of villages located very closely to the National Park and the changes of its boundaries, it seems that the protected area was interpreted as a land reserve for colonization projects in the future. - The existing planning documents show a well developed basis for environmental planning. It is worth mentioning especially the case of the Florida Province Development Plan. - With reference to the internal spatial structure four sub-centers were identified: Los Negros, Mairana, Samaipata and Comarapa. Whereas Los Negros and Mairana assumed the function of economic centers, the principle administrative functions as well banking facilities and (limited) possibilities of higher education are still concentrated in Samaipata and Comarapa, the main colonial settlements of the region. Due to its intensive relations to the villages on the National Park boarder, all of them should be integrated in a future buffer-zone. - Tourism is concentrated around Samaipata, eco- tourism is still a rather exceptional activity in the region. - The institutional landscape of the region show a number of regional based institutions, an interesting potential for a self-determined development process. Finally, recommendations are presented to extend multidisciplinary investigations on buffer-zones in the future. The study forms part of a comparative investigation on different regions in the eastern slope of the Andes. For further information see as well the publications on the Alto Mayo region in Peru and the eastern buffer-zone of the Sangay National Park in Ecuador.
Keywords: Pufferzone; Raumordnung; wirtschaftliche Zonierung; Bolivien; Regionalplanung; bufferzone; economic zonification; Bolivia; regional planning; ddc:910